Interferon Regulatory Factor 3 Deficiency Induces Age-Related Alterations of the Retina in Young and Old Mice - Zhang, Xi; Zhu, Jingyi; Chen, Xianjun; Jie-Qiong, Zhang; Li, Xue; Luo, Linlin; Huang, Huang; Liu, Wenyi; Zhou, Xinyuan; Yan, Jun; Lin, Sen; Ye, Jian (Frontiers in Cellular Neuroscience, 2019)
Age-related changes in visual function and retina structure are very common in aged animals, but the underlying mechanisms of these changes remain unclear. Here we report that the expression of interferon regulatory factor 3 (IRF3), a critical immune regulatory factor, is dramatically down-regulated in mouse retinas during aging. To address the role of IRF3 in the retina, we examined the structure and function of retinas in young (3-4 months) and old (22-24 months) Irf3-/- mice in comparison to age-matched wildtype (WT) mice. We found that IRF3 deletion resulted in impaired electroretinogram (ERG) responses and decreased retinal thickness in both young and old mice. In addition, numerous synapses of the outer plexiform layer (OPL) were found obviously extending into outer nuclear layer (ONL) in Irf3-/- mice, along with a reduction of the average synapse density in the OPL. These changes suggest that IRF3 deletion may accelerate retinal senescence. In support of this hypothesis, a number of classic senescence-associated markers were found in remarkably elevated level in Irf3-/- retina, including p53, p16INK4a, inositol-requiring enzyme 1α (IREα), p-H2A.X and promyelocytic leukemia protein (PML). Overall, our results indicate that maintenance normal IRF3 levels is necessary for retinal structure and function and suggest that IRF3 is an important regulator of retinal senescence.